P04 Childhood morbidities after neonatal abstinence syndrome: a systematic review and meta analysis. (25th October 2020) - Rees, P; Stilwell, P; Bolton, C; Arkillioglu, M; Carter, B; Gale, C; Sutcliffe, A
Abstract : Background: Neonatal abstinence syndrome (NAS) has garnered international attention by reaching epidemic proportions in countries such as the USA. Given the surge in incidence, the potential impact of NAS on the developing infant's physiology, and the prevalence of adverse childhood experiences amongst this cohort, it is critical that we gain a handle on the future health and wellbeing of this population. Methods: We undertook a systematic review and meta-analysis exploring the association between NAS and adverse childhood outcomes. A search strategy was developed in Medline Ovid and adapted for other databases. An all-language search was conducted across 11 databases between January 1, 1975, and September 3, 2019. Observational studies of children between 28 days and 16 years of age, in whom a previous diagnosis of opiate-related NAS was documented, were included. Of 5864 studies identified, 580 full-text articles were screened for eligibility, independently by three reviewers, and data from 14 studies were extracted. Data were pooled using a random-effects model and presented as crude and adjusted Odds Ratios (aOR) with accompanying 95% confidence intervals and I 2 statistics. Results: Fourteen studies were included, five of which were suitable for meta-analysis. This included 11, 549 children with previous NAS and 1, 463, 846 children without previous NAS, aged 0–16 years. Studies were conducted in the USA (n=7), Australia (n=4), the UK (n=2), and Norway (n=1). There was a strong association between NAS and: subsequent child abuse (aOR 6.49 (4.46, 9.45, I 2 =52%)), injuries and poisoning (aOR 1.34 (1.21, 1.49, I 2 = 0%)), and conduct disorders (aOR 1.72 (1.19, 2.48, I 2 =0%)). Studies consistently demonstrated increased incidence of strabismus and nystagmus after NAS. There was a weak association between NAS and speech and language impairment (crude OR 2.81 (1.82, 4.33, I 2 =26%)); as well as emotional and behavioural disorders (crude OR 4.29 (3.13, 5.88, I 2 =0%)). Conclusion: NAS was significantly associated with future child abuse, injuries and poisoning, certain mental health diagnoses, and visual impairment. This review does not suggest causation but highlights important associations requiring urgent further investigation and targeted intervention to positively impact the life course trajectories of this growing cohort of children.